Bamboo Craft Development Strategy in the Industrial Era 4.0 Towards Society 5.0 Gintangan Village - Mohammad Iskandar; Jemi Cahya Adi Wijaya; Adetiya Prananda Putra (Publikasi Indonesia, 2024)
The creative economy sub-sector contributed Rp. 1,153.4 trillion or to the total National GDP, 15.2% of the workforce, and 11.9% of exports (Kominfo, 2022). One of the villages that has a creative industry is Gintangan Village. The majority of Gintangan Village residents have a livelihood, namely, craftsmen. Many people work as craftsmen to fulfill their daily needs. However, bamboo handicraft centers are currently considered to still use conventional business so the management and organization are not well organized. This research aims to formulate a development strategy for the Industrial Revolution 4.0 towards Society 5.0. This research uses Ministry of Industry indicators namely, 1) management and organization; 2) people and culture; 3) products and services; 4) technology; and 5) factory operations. This research method uses descriptive qualitative with SWOT analysis. The results of this study indicate that the potential of the bamboo handicraft industry includes fine fiber bamboo, strategic location, adequate human resources, a wide variety of bamboo handicrafts, bamboo handicraft tourism villages, good handicraft branding, and professional staff. The highest strength factor is being a Tourism Village in the field of bamboo handicrafts and the main weakness factor is the lack of knowledge of digital technology marketing. The highest opportunity factor is the support of mass media promotion and the main threat factor is uncertain global dynamics and the lack of public awareness of the importance of technology application.